INVESTIGATION OF THE EFFECTS OF BRAND LOYALTY AND HAPPINESS ON CONSUMERS’ IMPULSE BUYING TENDENCY - Sara Shakeri, Fereshteh Einollahpour Gharigh (International Journal of Research Science and Management, 2016)
The concept of happiness has been extensively studied in psychology but has received limited attention in the marketing field as the antecedent of the consumer behavior aspects such as impulse buying and brand loyalty. To test the hypothesis we conducted the survey of Iranian consumers using the convenience sampling method. Questionnaires were distributed to university, and college students. This research considers the effect of happiness on impulse buying and brand loyalty and examines how brand loyalty affects impulse buying. The regression analysis was used to assess the assumed effects. The assumption of the existence of the relationship between happiness, impulsive buying and brand loyalty was not supported, revealing that this phenomenon still requires further scientific attention. Contrary to the predictions the brand loyalty was positively related to the affective aspect of impulsive buying tendency. This study contributes to the understanding of the reasons for the brand loyalty and impulse buying, where the latter is associated with negative outcomes with respect to the individual